2021
DOI: 10.1186/s13021-021-00175-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tree species diversity and stand structure on carbon stocks of homestead forests in Maheshkhali Island, Southern Bangladesh

Abstract: Background The homestead forests of Bangladesh occupy 0.27 million hectares (10% of the total forested area) and have potential to store carbon (C) and conserve biodiversity. Small scale forestry practices, however, are lacking reliable estimation of C stocks and tree species diversity. This may hinder successful implementation of REDD + and similar mechanisms as they concentrate on large-scale forests. This study aimed to estimate the above- and below-ground carbon stocks in homestead forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…However, the result in this study was opposite to the above claim proving that parkland AFS accounts for a high amount of carbon stock compared to the other studied AFS having a lower number of individual trees with less diversity. Therefore, the result indicated that the stand structure and number of individual trees in the study area have a greater impact on increasing the carbon stock than the species diversity (Baul et al 2021). This study also indicated that the species diversity has a significant positive relationship with aboveground carbon.…”
Section: Socioeconomic Characteristics Of Respondentsmentioning
confidence: 90%
“…However, the result in this study was opposite to the above claim proving that parkland AFS accounts for a high amount of carbon stock compared to the other studied AFS having a lower number of individual trees with less diversity. Therefore, the result indicated that the stand structure and number of individual trees in the study area have a greater impact on increasing the carbon stock than the species diversity (Baul et al 2021). This study also indicated that the species diversity has a significant positive relationship with aboveground carbon.…”
Section: Socioeconomic Characteristics Of Respondentsmentioning
confidence: 90%
“…Hence, even though livestock farming emits greenhouse gases all year round, these gases can be offset through carbon sequestration (Figure 2). The sequestration concept is very complex [130] and requires details in terms of compositions, as diversity in the forest ecosystem has a significant effect on carbon sequestration [131][132][133][134]. For instance, aged trees store more atmospheric carbon than young trees [135][136][137].…”
Section: Potential Impacts Of Forestry On the Environmental Footprint...mentioning
confidence: 99%
“…Therefore, the biophysical effects of forests on soil and water cycle promote, erosion control, water conservation, and nutrient cycling, making forests essential components of resilient and sustainable landscapes. The sequestration concept is very complex [130] and requires details in terms of compositions, as diversity in the forest ecosystem has a significant effect on carbon sequestration [131][132][133][134]. For instance, aged trees store more atmospheric carbon than young trees [135][136][137].…”
Section: Potential Impacts Of Forestry On the Environmental Footprint...mentioning
confidence: 99%
“…Despite the significant number of community forests in Nepal, there is often a lack of detailed information regarding essential technical aspects such as species diversity, stand structure, and carbon stocks (Anup, 2017;Poudyal et al, 2019). These metrics are critical for understanding the role of forests in providing ecosystem services such as carbon sequestration, soil conservation, and biodiversity conservation (Mandal et al, 2013;Bhandari et al, 2021;Baul et al, 2021). Therefore, there is a growing need for assessments studies in community forests in different regions that can provide detailed information about these technical aspects and their implications for ecosystem services (Paudyal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%